Computer-Aided Design and Computer-Aided Manufacturing Cutting Guides in Eminoplasty for the Treatment of Temporomandibular Joint Dislocation. Issue 2 (March 2019) - Xu, Chunwei; Liu, Hanghang; Du, Wen; Wang, Yiyao; Hu, Jian; Luo, En
Abstract : Objective: Temporomandibular joint (TMJ) dislocation means the condyle moves out of the normal position. There are several treatments for TMJ dislocation, including conservative treatment, injection treatment, minimally invasive treatment, and open surgical treatment. In this study, we tried to review the literature related to the augmentation of the articular eminence and proposed a modified eminoplasty technique of TMJ dislocation by computer-aided design and computer-aided manufacturing (CAD/CAM) cutting guides. Methods: The literature on eminoplasty for TMJ was reviewed with 3 charts. Besides, 2 (67 and 69 years old) patients with chronic recurrent dislocation were treated by the CAD/CAM-guided surgical technique in our study, and postoperative measures were recorded to verify the safety and effectiveness regarding this technique. Results: A total of 28 studies (including 268 patients) of the augmentation of the articular eminence have been reported since 1967, including the 2 present patients. According to the analysis of the recurrence and complications in the review, we found the modified technique had an obvious advantage. The technique with cutting guides was also found having higher accuracy. Conclusion: The modified technique was a reliable method when treating the TMJ dislocation, and the combination of CAD/CAM cutting guides was useful for more accuracy, even reduced the operation difficulty.